Thermal geological model of the city of Guayaquil, Ecuador. (March 2017) - Soriano, Guillermo; Espinoza, Tania; Villanueva, Ruben; Gonzalez, Inmaculada; Montero, Andres; Cornejo, Mauricio; Lopez, Katthy
Abstract : Highlights: Thermal response tests (TRTs) are conducted in nine sites in the city of Guayaquil, Ecuador. Geological characterization of the selected sites is performed. Maps of thermal properties of the city are built. A thermal model of a heat exchanger working in Guayaquil is presented. Abstract: A thermal-geological model of the city of Guayaquil, Ecuador is presented, by thorough drill core studies and thermal response tests (TRTs) at ten representative locations. The aim of the project was to complete an analysis of the geological and thermal properties to define their suitability for ground source based heating ventilating and air conditioning (HVAC) systems. The first task consisted of performing mineralogical and geotechnical analysis of the samples using X-ray diffraction, optical microscopy, and grain size analysis tests to identify the litho-stratigraphy of ten points or areas in the city of Guayaquil. Simultaneously, field thermal response tests were completed to collect data on thermal properties of the soil in the ten locations. The geological and thermal response test results were used to develop representations of the city lithography as well as its thermal conductivity, resistivity, and undisturbed ground temperature results. These maps constitute a tool to design geothermal cooling systems and define the suitability of using the soil as a heat sink for cooling systems.